APPLYING QUANTUM LEARNING DESIGN FRAMEWORK TO IMPROVE LISTENING ABILITY - HARDIANTI HARDIANTI (Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Luwuk, 2019)
Students had their own uniqueness, no except with their learning style. They may be visual, auditory, or kinesthetic learners. Teacher should find suitable and adaptable method for the students’ modalities. The researcher applied quantum learning design framework in listening class. The researcher wanted to find out the significance difference between applying quantum learning design framework and dictogloss technique. This research used quasi experimental with two groups pre test and post test design. The sample of the research was taken from the ninety six students of tenth grade at MAN 2 Parepare in academic year of 2014/2015. The research took thirty six students in class X 2 and X 3 as the sample. The result of the data analysis showed that there was an improvement of the students’ means score both experimental and control class. However, the students’ means score in experimental class was higher than the students’ in control class. The hypothesis testing showed that the null hypothesis was rejected and the alternative hypothesis was accepted. It indicates the significance difference between the listening ability of the students who were taught through Quantum Learning design framework and the listening ability of the students who were taught through dictogloss technique.Keyword: Quantum, Framework, Listening